2013
DOI: 10.1186/1471-2407-13-73
|View full text |Cite
|
Sign up to set email alerts
|

Multicellular tumor spheroid models to explore cell cycle checkpoints in 3D

Abstract: BackgroundMultiCellular Tumor Spheroid (MCTS) mimics the organization of a tumor and is considered as an invaluable model to study cancer cell biology and to evaluate new antiproliferative drugs. Here we report how the characteristics of MCTS in association with new technological developments can be used to explore the regionalization and the activation of cell cycle checkpoints in 3D.MethodsCell cycle and proliferation parameters were investigated in Capan-2 spheroids by immunofluorescence staining, EdU incor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
92
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(111 citation statements)
references
References 25 publications
14
92
0
1
Order By: Relevance
“…This might explain the drastic decrease of RPS6 phosphorylation -from high levels in the outer two-cell-layer-thick zone to low levels in the deeper areas. Of note, cell proliferation also decreased gradually in the inner zones of the spheroids, as demonstrated previously (Grimes et al, 2014;Laurent et al, 2013). However, when mTOR activity was inhibited, RPS6 phosphorylation was lost but Ki67 remained, indicating that there is no direct correlation of RPS6 phosphorylation with cell proliferation.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This might explain the drastic decrease of RPS6 phosphorylation -from high levels in the outer two-cell-layer-thick zone to low levels in the deeper areas. Of note, cell proliferation also decreased gradually in the inner zones of the spheroids, as demonstrated previously (Grimes et al, 2014;Laurent et al, 2013). However, when mTOR activity was inhibited, RPS6 phosphorylation was lost but Ki67 remained, indicating that there is no direct correlation of RPS6 phosphorylation with cell proliferation.…”
Section: Discussionsupporting
confidence: 72%
“…6E). The proliferation marker Ki67 exhibited a well-described decrease of Ki67 + cells from the outside to the core of the spheroid (Grimes et al, 2014;Laurent et al, 2013). Ki67 + cells were significantly reduced in the treated samples as compared to the control ( Fig.…”
Section: Altered Signaling In 2d Vs 3d Cultures Upon Akt-mtor And/ Ormentioning
confidence: 78%
“…Furthermore, in 3D models, cells seem to express distinct genes usually associated with drug resistance that were also found in in vivo animal studies (58). Factors, such as alteration of chromatin structure, apoptosis inhibition, cell cycle and permeability, make the MCTS a more reliable and predictable drug testing in vitro model compared to 2D monolayer models (29,37,(62)(63)(64). Radiation resistance has also been linked to spheroid models in the past.…”
Section: Anticancer Researchmentioning
confidence: 88%
“…HCT116 colon adenocarcinoma cells (ATCC) were cultured in DMEM (Invitrogen; Thermo Fisher Scientific, Inc., Waltham, MA, USA) containing 10% foetal calf serum (FCS), 2 mM/l glutamine and penicillin/streptomycin in a tissue culture incubator (humidified atmosphere of 5% CO 2 at 37˚C). Spheroids were prepared as previously described (9). Briefly, 500 cells/well were distributed in ultra-low attachment 96-round bottom well plates.…”
Section: Methodsmentioning
confidence: 99%
“…Several reports have shown that spheroid growth results in the generation of a hypoxia and nutrient gradients (7)(8)(9) where cells localized in the inner region exit the cell cycle and enter a G0 quiescent state. The induced cell quiescence in the spheroid central region mimics the situation observed in vivo in microtumor domains and the subsequent resistance to classical chemotherapeutic agents (10,11).…”
Section: Introductionmentioning
confidence: 99%